The role of frequency in language acquisition: input-output relationship - Dabašinskienė, Ineta (Vilnius University Open Series, 2022)
Children acquire the language system very fast and rather easily due to their sensitivity to lexical and grammatical structures and their distribution. Additionally, a stable distribution of linguistic structures in the input could help children to recognize these structures. We are aware of the fact that in many languages children start with nouns followed by verbs, therefore the distribution of the main parts of speech could signal important information about the syntactic structure of the early child speech.The primary aim of this study is to investigate the frequency distribution of parts of speech in child speech and input in Lithuanian. The analysis focuses on nouns, verbs, adjectives, adverbs, and pronouns, as these are the main elements constructing the syntactic relations of the utterance. The Lithuanian corpora have been studied that included the data of two children of different sex and their input. The main findings come from the analysis of the data of approximately one year (from the age of 1;7 to 2;8) and demonstrate an interesting result: a high degree of stability in the distribution of the target categories in the input data and a close correlation between input and output in later stages of children’s language development.
Keywords: Lithuanian child language acquisition; frequency; input; parts of speech; usage-based approach